Problems of minimal and maximal aerodynamic resistance - Plakhov, Alexander
This is a review of results recently obtained by the author, related to problems of the body of minimal and maximal resistance. The cases of purely translational motion, as well as (rotational & translational) motion are considered. The notions of rough body and law of scattering on a body are discussed. Connections with the Monge-Kantorovich problem of optimal mass transportation are revealed, and applications to the Magnus effect and retroreflectors are discussed.